The effect of eight weeks of respiratory muscle training with two different protocols on performance and ventilatory factors in soccer players - Abdolrahman Najafi; Khosro Ebrahim; Sajad Ahmadizad; Gholam Reza Jahani Ghaeh Ghashlagh (Shahid Beheshti University, 2018)
Purpose: The aim of this study was to investigate the effect of eight weeks of respiratory muscle training(RMT) with two different protocols on performance and ventilatory factors in soccer players.Methods: Thirty young trained soccer players between 16-19 years of age were randomly divided into 3groups: experimental A (n=10), experimental B (n=10) and control (n=10). All groups carried out their regularsoccer training with a 8-week RMT period of 1×30 breaths twice daily, five days weekly at 55% (experimentalA) or 15% (control) maximal inspiratory pressure (MIP) or 1×50 breaths twice daily, five days weekly at 40%MIP (experimental B). MIP; standard spirometry; Yo-Yo intermittent recovery test level 1 (YYIRT level 1);Repeated High-Intensity Endurance Test (RHIET) and Running-based Anaerobic Test (RAST) were measuredbefore and after the period. One-way ANOVA was used to analyze the data.Results: MIP, VO2max, running distance, and repeated sprint ability (RSA) increased significantly and ratingof perceived exertion (RPE), rating of perceived breathlessness (RPB) and blood lactate concentrationdecreased significantly in EXP1 and EXP2 groups compared to Control group (p<0.05) but there was nosignificant difference in ventilatory volumes (VC, FVC, FEV1.0, MVV, and PEF) among groups (p>0.05).Conclusions: The results showed that RMT is a good complement to enhance performance in soccer playersand should be included in their physical fitness training.